Uniting Trump’s America: Rhetorical constructions in Donald Trump’s 2017 inaugural address - Kauffman, Joseph E. (Kansas State University, 2021)
The diversity present within the United States presents a crucial question for its populace: what does it mean to be an American? No one is better positioned to answer this query than the president, who does so through rhetorical constructions of national identity. A functional polity requires some measure of common identity and constructing it is an important task for the country’s only nationally elected and most visible representative. Yet scholars well identify Trump and his rhetoric as dangerously divisive. This paradox forces one to wonder: how did Trump attempt the task of rhetorically constructing an American national identity? The thesis that follows attends to this question with an analysis of Trump’s attempts to rhetorically construct the American people via his inaugural address. In addition to the how of Trump’s attempts at construction, I also consider who these attempts identify as true Americans and the effects that these attempts may induce in the American people. I first place this question within the context of previous research on presidential rhetoric and national identity. Scholars identify the tasks of generating, re-articulating, and maintaining national identity as key features of the modern U.S. presidency. Audiences are rhetorical constructs and these constructions involve rhetors creating groups and identities. National identity is one such construction. It is discursively created, distinct from concrete markers of inclusion (such as legally granted citizenship), and perpetually contested in the public sphere. Next, I explicate why a rhetorical criticism of the 2017 inaugural address is the best way to conduct my investigation. Presidents traditionally use their inaugurals to propose a message of unity that reaches beyond their supporters and establishes a binding vision of national identity. Given this and their epideictic characteristics, inaugurals are fertile fields for harvesting rhetorical propositions of American identity. This critical analysis focuses on three areas of Trump’s inaugural: 1) the type of imagery Trump employs, 2) the ideas and ideographs Trump invokes and utilizes, and 3) how Trump constructs through the use of delineation and divisiveness. I then proceed with my analysis. I argue Trump did forward a consistent though exclusionary vision of American identity. My analysis shows this identity is America as a white Christian nation, a definition formed through Trump’s utilization of a religious-based rhetoric of white Christian nationalism. I define the contours of that white Christian nationalism and its rhetoric. I then elucidate how its presence in Trump’s inaugural is revealed through his rhetorically invoking themes of blood, apocalypticism, and nostalgia. Lastly, I place my findings in context and discuss their broader implications. Ultimately, this progresses along two lines. First, Trump’s inaugural represents an aberration in presidential constructions of national identity. Specifically, Trump constructs national identity more narrowly than other contemporary office holders and his articulation of American-ness is less based in shared ideations and values. Second, the propagation of white Christian nationalist rhetoric is deleterious to American liberalism and pluralism. I argue for the importance of considering religious themes in political discourse and that failure to do so may result in scholars missing valuable context and nuance into events such as those that took place at the U.S. Capital on January 6, 2021.
Keywords: Rhetoric; National identity; U.S. Presidency; Religion; Public address; Political communication